2007
DOI: 10.1109/tuffc.2007.596
|View full text |Cite
|
Sign up to set email alerts
|

Squeeze film effect for the design of an ultrasonic tactile plate

Abstract: Abstract-Most tactile displays currently built rely on pin-based arrays. However, this kind of tactile device is not always appropriate when we need to give the illusion of finely textured surfaces. In this paper, we describe the squeeze film effect between a plate and a finger, and we use this effect to design an ultrasonic tactile plate. The plate is actuated by piezoelectric ceramics. Ultrasonic vibrations are thus produced and are capable of generating the squeeze film effect. This enables us to simulate v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(141 citation statements)
references
References 12 publications
3
136
0
2
Order By: Relevance
“…Flexural vibrations at this ultrasonic frequency create a squeeze film of air between the plate surface and the finger, thus reducing the friction between the plate and the fingertip as the amplitude of the applied voltage is increased. The mechanisms of friction reduction have been discussed more fully in Biet et al [7]. We performed a preliminary user study and found that the squeeze film effect between the glass plate and the finger starts to be felt at a vibration amplitude of around 1.5 microns.…”
Section: Tactile Pattern Display (Tpad)mentioning
confidence: 80%
“…Flexural vibrations at this ultrasonic frequency create a squeeze film of air between the plate surface and the finger, thus reducing the friction between the plate and the fingertip as the amplitude of the applied voltage is increased. The mechanisms of friction reduction have been discussed more fully in Biet et al [7]. We performed a preliminary user study and found that the squeeze film effect between the glass plate and the finger starts to be felt at a vibration amplitude of around 1.5 microns.…”
Section: Tactile Pattern Display (Tpad)mentioning
confidence: 80%
“…This is easily verified in figure 2, where modes with less neighbors appear to be wider, so we will eliminate vibration modes at 25.7kHz and 43.2kHz. Finally, we use the vibration mode at 31.2kHz because it is at a lower frequency and produces then a larger half-wavelength [3]. The simulation results of this vibration mode are depicted in figure 3.…”
Section: Plate's Designmentioning
confidence: 99%
“…Winfield et al used a small piezoelectric patch completely covered by a glass disc [15], while Biet et al designed a rectangular tactile plate made with copper-beryllium [3]. Both of these devices render tactile sensations on a large area by using a flexural vibration mode with a wavelength of about 3cm.…”
Section: Introductionmentioning
confidence: 99%
“…A more recently introduced technique is to modulate the friction force between the finger and a mechanically grounded active surface. The friction force modulation can be achieved, for instance, by electrostatic fields [26], ultrasonic amplitude modulation [27], surface acoustic waves [28] or with the squeezed film effect [29], [30].…”
Section: Roughness and Texture In Manufacturing And Virtual Realitymentioning
confidence: 99%